2010
DOI: 10.1016/j.febslet.2010.11.015
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C and mitochondrial permeability transition pore in the neuroprotective effect of ceramide in ischemia-induced cell death

Abstract: a b s t r a c tIn this study, we investigated the role of protein kinase C (PKC) and mitochondrial permeability transition pore (mPTP) on the effect of ceramide in an in vitro model of ischemia in SH-SY5Y neuroblastoma cells. In ischemic cell viability studies, a dual effect of ceramide was observed, depending on ceramide concentration. PKC isoforms are involved in the protective effect of low concentrations of ceramide. During ischemia, ceramide treatment leads to an increase in the formation of reactive oxyg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
22
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(22 citation statements)
references
References 24 publications
0
22
0
Order By: Relevance
“…2) result from Pb-induced MPTP opening. Moreover, mitochondrial injury can cause ROS production, while increased formation of ROS can induce the MPTP opening (Agudo-López et al 2011;Xu et al 2014). To further investigate the effect of MPTP opening on apoptosis in Pb-exposed rPT cells, translocation event of cyt-c from mitochondria to the cytosol was determined by western blot analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…2) result from Pb-induced MPTP opening. Moreover, mitochondrial injury can cause ROS production, while increased formation of ROS can induce the MPTP opening (Agudo-López et al 2011;Xu et al 2014). To further investigate the effect of MPTP opening on apoptosis in Pb-exposed rPT cells, translocation event of cyt-c from mitochondria to the cytosol was determined by western blot analysis (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Agudo-Lopez and collaborators (1) previously demonstrated that PKC activation mediates the protective actions of ceramide during ischemia through increased formation of ROS, which leads to the opening of MPTP. Opening of MPTP prevents mitochondrial Ca 2ϩ overload, mitochondrial swelling, and cell death (1). PKC-ε is one of PKC isozymes involved in stabilizing mitochondria by modifying MPTP opening (7).…”
Section: Discussionmentioning
confidence: 99%
“…We determined that the activation of the δ-opioid receptor enhances PKC expression. PKC stimulation inhibits the apoptosis of different types of cells (38)(39)(40). Meanwhile, PKC also participates in the protection against hepatic ischemia reperfusion injury and is involved in the processes of cellular proliferation and apoptosis (19,41).…”
Section: Discussionmentioning
confidence: 99%